Silicon-based composite negative electrode material and preparation method thereof
By introducing niobium-based composite oxides and metal nanoparticles into the silicon-based anode material of solid-state batteries, the problems of low conductivity and volume expansion of silicon-based anode materials are solved, and the safety and cycling performance of solid-state batteries are significantly improved.
Patent Information
- Application Number
- CN202411588380.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-18
AI Technical Summary
The silicon-based negative electrode material has poor conductivity in solid-state batteries, resulting in volume expansion during charging and discharging, poor circulation performance, and prone to side reactions with solid-state electrolytes at low potentials, resulting in reduced safety and first-time Coulomb efficiency.
A silicon-based composite negative electrode material is used, which includes a composite of a silicon-based material and a niobium-based composite oxide, and metal nanoparticles supported on the composite, at least a portion of the niobium-based composite oxide is coated on the surface of the silicon-based material. In the preparation method, the negative electrode material is obtained by mixing the composite of the silicon-based material and the niobium-based composite oxide with the supported metal source solution and performing a reduction treatment.
The conductivity and lithium embedded potential of the silicon-based composite negative electrode material are improved, side reactions with solid electrolytes are avoided, volume expansion is alleviated, and the safety, circulation performance and first-time Coulomb efficiency of solid-state batteries are significantly improved.
Smart Images

Figure FT_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of negative electrode materials for lithium batteries, and in particular to a silicon-based composite negative electrode material and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of consumer electronics, new energy vehicles and other fields, lithium-ion batteries have played an increasingly important role. All-solid-state lithium batteries based on solid-state electrolytes are known as the safest battery system.
[0003] The characteristics of silicon-based negative electrode materials in solid-state batteries have a great influence on the energy density, rate performance, cycle life and safety of solid-state batteries to a great extent. The research and development of silicon-based negative electrode materials with excellent electrochemical performance has always been the focus of attention in the field of solid-state batteries. However, due to the poor conductivity of silicon-based negative electrode materials, there will be a dramatic volume expansion when lithium is repeatedly inserted and removed during the charging and discharging process, which makes the electrode capacity of the solid-state battery decay rapidly and the cycle performance is poor. In addition, at low potential, solid electrolytes such as sulfides or halides in solid-state batteries are prone to side reactions with silicon-based negative electrode materials, and the lithium insertion potential of silicon-based negative electrode materials is low, which is easy to produce lithium dendrites, which leads to the decrease of battery cycle performance, safety and first coulomb efficiency. The above technical problems have become bottlenecks in the practical application and development of silicon negative electrode materials in solid-state batteries.
[0004] In order to better optimize the electrochemical performance of silicon-based solid-state batteries, the common methods of modifying silicon-based materials are mainly: (1) Multi-dimensionality of silicon. The use of silicon materials with special nanostructures, such as silicon nanosheets, porous silicon, silicon nanowires, etc., can increase the specific surface area, provide more electrochemically active sites, and slow down the volume effect and pulverization of silicon particles. However, this method will cause the side reactions of the solid electrolyte in the battery to become more serious, thereby greatly reducing the first coulombic efficiency of the battery; (2) Design of silicide alloys. The metal itself has excellent mechanical properties. When combined with the silicon negative electrode to form an alloy, it can effectively buffer the volume change of the silicon negative electrode material during lithium insertion and extraction, thereby achieving the purpose of stabilizing the structure. However, due to the use of metals such as magnesium, nickel, and chromium, this method is relatively expensive. (3) Silicon is combined with an active material with excellent conductivity, such as silicon-carbon material. This composite material combines the high capacity of silicon with the high conductivity and cycle performance of graphite materials, which can improve the overall performance of the battery. However, the negative electrode material is prone to side reactions with solid electrolytes (sulfides or halides, etc.) at low potentials. At the same time, due to the lithium insertion potential of carbon (0.1Vvs.Li / Li + ) is low, which easily leads to lithium dendrites, thus causing the battery's cycle performance to deteriorate and safety issues.
[0005] In summary, although certain improvements have been made to the silicon-based negative electrode materials in solid-state batteries, which have improved the overall performance of solid-state batteries to a certain extent, the silicon-based negative electrode materials in the prior art are difficult to solve the problems existing in the above-mentioned silicon-based negative electrode materials at the same time. Summary of the invention
[0006] In view of the above problems of the prior art, the present application provides a silicon-based composite negative electrode material and a preparation method thereof, which improves the conductivity and lithium insertion potential of the silicon-based composite negative electrode material, avoids the side reaction between the silicon-based material and the solid electrolyte of the solid-state battery at low potential, and alleviates the volume expansion of the silicon-based material during the charging and discharging process, effectively improving the comprehensive performance of the silicon-based solid-state battery. The specific technical solution is as follows:
[0007] On the one hand, the present application provides a silicon-based composite negative electrode material, which includes a composite of a silicon-based material and a niobium-based composite oxide, and metal nanoparticles loaded on the composite, and at least a portion of the niobium-based composite oxide is coated on the surface of the silicon-based material.
[0008] In a possible implementation manner, the negative electrode material satisfies at least one of the following characteristics:
[0009] The thickness of the niobium-based composite oxide coated on the surface of the silicon-based material is 200nm-2um;
[0010] The loading thickness of the metal nanoparticles on the composite is 30nm-500nm.
[0011] In a possible implementation manner, the negative electrode material satisfies at least one of the following characteristics:
[0012] The median particle size of the metal nanoparticles is 10nm-150nm;
[0013] The particle size of the silicon-based material is 500nm-10um.
[0014] In a possible implementation manner, the material of the metal nanoparticles includes at least one of silver, gold, copper, magnesium, and tin.
[0015] In a possible implementation, the niobium-based composite oxide includes niobium and doping elements, and the doping elements include at least one of transition elements other than niobium, phosphorus, strontium, boron, potassium, carbon, calcium, and magnesium.
[0016] On the other hand, the present application provides a method for preparing a silicon-based composite negative electrode material, which is applied to the negative electrode material described in the above embodiment, comprising:
[0017] S1: providing a composite of a silicon-based material and a niobium-based composite oxide;
[0018] S2: mixing the composite of the silicon-based material and the niobium-based composite oxide with a loaded metal source solution and stirring for a period of time to obtain a composite intermediate solution;
[0019] S3: performing reduction treatment on the composite intermediate solution to obtain a silicon-based composite negative electrode material.
[0020] In a possible implementation manner, the composite intermediate solution is subjected to reduction treatment to obtain a silicon-based composite negative electrode material, comprising: mixing the composite intermediate solution with a reducing agent and stirring for a period of time to obtain a reduced composite intermediate solution, and drying the reduced composite intermediate solution to obtain the silicon-based composite negative electrode material.
[0021] In a possible implementation manner, the preparation method satisfies at least one of the following characteristics:
[0022] The stirring time in the stirring process in step S2 is 1-5h, and the stirring speed is 200-600r / min;
[0023] The stirring time in the stirring process in step S3 is 1-5h, and the stirring speed is 200-600r / min;
[0024] The drying temperature in the drying process in step S3 is 50-120° C., and the drying time is 12-36 hours.
[0025] In a possible implementation, a composite of the silicon-based material and the niobium-based composite oxide is provided, comprising:
[0026] S11: providing a mixed solution including a doping material, a niobium source and a silicon-based material;
[0027] S12: Grinding the mixed solution to obtain a precursor slurry;
[0028] S13: drying the precursor slurry for a period of time to obtain a precursor material;
[0029] S14: calcining the precursor material in an oxygen-free environment to obtain a composite of the silicon-based material and the niobium-based composite oxide.
[0030] In a possible implementation manner, the preparation method satisfies at least one of the following characteristics:
[0031] In the precursor slurry, the molar ratio of the doping material to the niobium source is 1:(2-30);
[0032] In the precursor slurry, the mass ratio of the silicon-based material to the niobium source is (10-85):1.
[0033] In the composite intermediate solution, the mass ratio of the supported metal source to the composite of the silicon-based material and the niobium-based composite oxide is 1:(45-90).
[0034] In a possible implementation manner, providing a mixed solution containing a doping material, a niobium source and a silicon-based material comprises:
[0035] S110: mixing the doping material and the first solvent in a certain ratio and stirring for a period of time to obtain a first mixed solution;
[0036] S111: mixing the niobium source and the second solvent in a certain ratio and stirring for a period of time to obtain a second mixed solution;
[0037] S112: mixing the silicon-based material and the third solvent in a certain ratio and stirring for a period of time to obtain a third mixed liquid;
[0038] S113: adding the first mixed solution and the second mixed solution to the third mixed solution, mixing and stirring for a period of time to obtain the mixed solution containing the doping material, the niobium source and the silicon-based material.
[0039] In a possible implementation manner, the preparation method satisfies at least one of the following characteristics:
[0040] The stirring time in the stirring process in steps S110, S111 and S112 is 2-10 hours, and the stirring speed is 200-600 r / min;
[0041] The stirring time in the stirring process in step S113 is 3-12 hours, and the stirring speed is 200-600 r / min;
[0042] The ball-to-material ratio in the grinding process in step S12 is (2-30):1, the ball milling time is 2-15h, and the ball milling speed is 100-500r / min;
[0043] The drying temperature in step S13 is 50-120°C and the drying time is 8-36h;
[0044] The calcination temperature in step S14 is 500-1200°C, the heating rate is 0.5-10°C / min, and the calcination time is 0.5-6h;
[0045] The oxygen-free environment in step S14 is formed by an inert atmosphere, and the inert atmosphere includes at least one of argon, hydrogen-argon mixed gas and nitrogen.
[0046] Based on the above technical solution, this application has the following beneficial effects:
[0047] (1) The negative electrode material in the present application includes a composite of a silicon-based material and a niobium-based composite oxide, and metal nanoparticles loaded on the composite, at least part of the niobium-based composite oxide is coated on the surface of the silicon-based material. By coating at least part of the niobium-based composite oxide on the surface of the silicon-based material, the tensile expansion deformation of the silicon-based material during the cycle is effectively suppressed and alleviated, and the silicon-based material is prevented from having a side reaction with the solid electrolyte at a low potential. At the same time, the negative electrode material has a higher lithium insertion potential, avoiding the problem that the silicon-based negative electrode material in the prior art is prone to form lithium dendrites at a lower lithium insertion potential, thereby further improving the safety, cycle performance and first coulomb efficiency of the solid-state battery; and loading metal nanoparticles on the composite of the silicon-based material and the niobium-based composite oxide can greatly improve the conductivity of the negative electrode material, optimize the electron conduction rate, thereby improving the rate performance of the solid-state battery, and can further alleviate the phenomenon that the negative electrode material will undergo drastic volume expansion when repeatedly deintercalating and extracting lithium during the charge and discharge process, which is beneficial to the battery to achieve stable high-rate charge and discharge, and improve the cycle life of the battery.
[0048] (2) In the present application, a composite intermediate solution is obtained by mixing a composite of a silicon-based material and a niobium-based composite oxide with a loaded metal source solution, thereby making the surface of the composite of the silicon-based material and the niobium-based composite oxide loaded with metal ions, and then a silicon-based composite negative electrode material is obtained after reduction treatment. The material is loaded with metal nanoparticles, thereby improving the electrical conductivity of the material, and its excellent ductility can alleviate the problem of volume expansion of silicon during charging and discharging, thereby improving the cycle stability of silicon-based solid-state batteries. In addition, the preparation method is simple and does not require the participation of any solid electrolyte. Therefore, it does not have high requirements on the water oxygen value of the production environment, greatly reducing the production difficulty and cost, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0050] Figure 1 The cycle performance diagram of the solid-state batteries prepared in Example 1 and Comparative Example 4. DETAILED DESCRIPTION
[0051] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0052] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0053] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0054] The following introduces the silicon-based composite negative electrode material provided in the embodiments of the present application. The negative electrode material includes a composite of a silicon-based material and a niobium-based composite oxide, and metal nanoparticles loaded on the composite, and at least a portion of the niobium-based composite oxide is coated on the surface of the silicon-based material. The niobium-based composite oxide and metal nanoparticles in the negative electrode material of the present application can effectively inhibit and buffer the tensile expansion deformation of the silicon-based material during the cycle, relieve stress concentration, maintain the stability of the electrode structure, reduce the pulverization and failure of the silicon material, and help to improve the cycle life of the all-solid-state battery; at the same time, the niobium-based composite oxide and the metal nanoparticles have very small volume expansion during the charging and discharging process, and can avoid the silicon-based material from having side reactions with the solid electrolyte at a low potential, protect the structural stability of the silicon-based material and the solid electrolyte, and help to improve the first effect and cycle performance of the material. At the same time, the negative electrode material has a higher lithium insertion potential, avoiding the silicon-based negative electrode material in the prior art from easily forming lithium dendrites at a lower lithium insertion potential, further improving the safety and cycle life of the solid-state battery. In addition, compared with the carbon layer in the prior art, the niobium-based composite oxide has a higher density, which can not only improve the volume energy density of the battery system, but also provide more redox electron pairs, and has a higher theoretical capacity. The high conductivity of the metal nanoparticles greatly improves the conductivity of the silicon-based composite negative electrode material, reduces the overpotential of the silicon-based negative electrode material, improves the lithium ion diffusion coefficient, and enhances the rate performance of the solid-state battery.
[0055] In some embodiments, the thickness of the niobium-based composite oxide coated on the surface of the silicon-based material is 200nm-2um. The upper limit of the thickness of the niobium-based composite oxide coated on the surface of the silicon-based material may be, but not limited to, 2um, 1.5um, 1.0um, etc., and the lower limit of the thickness of the metal nanoparticles loaded on the composite may be, but not limited to, 200nm, 201nm, 202nm, etc.; it can be understood that the loading thickness of the metal nanoparticles on the composite can also be any point value within the above range, which is not enumerated here. The appropriate coating layer thickness can control the diffusion rate of lithium ions, avoid premature reaction causing capacity loss, while maintaining good conductivity, and avoid excessive thickness that increases the diffusion resistance of lithium ions in the electrode material, thereby causing the capacity of the battery to decay. Preferably, the thickness of the niobium-based composite oxide coated on the surface of the silicon-based material is 300-700nm. Further preferably, the thickness of the niobium-based composite oxide coated on the surface of the silicon-based material is 400nm.
[0056] In some embodiments, the niobium-based composite oxide includes niobium and doping elements, and the doping elements include at least one of transition elements, phosphorus, strontium, boron, potassium, carbon, calcium, and magnesium other than niobium. Preferably, the doping elements include at least one of titanium, silver, aluminum, boron, copper, potassium, zirconium, tungsten, molybdenum, calcium, zinc, cobalt, iron, magnesium, manganese, chromium, phosphorus, bismuth, vanadium, strontium, and barium. Adding doping elements to the niobium-based composite oxide can further buffer the volume change caused by the insertion and extraction of lithium ions, reduce the cracking and pulverization of the material structure, and maintain the integrity of the electrode. At the same time, the addition of doping elements can promote the transmission of lithium ions in the material, thereby improving the capacity and cycle stability of the negative electrode material. Further preferably, the doping element is zinc. Using zinc as the doping element, the stability of the prepared negative electrode material is better.
[0057] In some embodiments, the loading thickness of the metal nanoparticles on the composite is 30nm-500nm. The upper limit of the loading thickness of the metal nanoparticles on the composite may be but not limited to 500nm, 490nm, 480nm, etc., and the lower limit of the loading thickness of the metal nanoparticles on the composite may be but not limited to 30nm, 31nm, 32nm, etc.; it can be understood that the loading thickness of the metal nanoparticles on the composite can also be any point value within the above range, which is not enumerated here. By limiting the loading thickness, the metal nanoparticles can have a sufficiently large specific surface area, thereby providing more electrochemical reaction active sites, improving the ion transfer efficiency, and further reducing the interface side reactions, alleviating the volume expansion of silicon-based materials, and improving the cycle performance and safety of the battery. Preferably, the loading thickness of the metal nanoparticles on the composite is 30-100nm. Further preferably, the loading thickness of the metal nanoparticles on the composite is 80nm.
[0058] In some embodiments, the median particle size of the metal nanoparticles is 10nm-150nm. The upper limit of the median particle size of the metal nanoparticles may be, but not limited to, 150nm, 149nm, 148nm, etc., and the lower limit of the median particle size of the metal nanoparticles may be, but not limited to, 10nm, 11nm, 12nm, etc.; it is understandable that the median particle size of the metal nanoparticles may also be any point value within the above range, which is not enumerated here. By limiting the particle size of the metal nanoparticles, the conductivity of the negative electrode material can be improved to a certain extent, while avoiding the problem of poor conductivity of the negative electrode material due to excessive particle size.
[0059] In some embodiments, the material of the metal nanoparticles includes at least one of silver, gold, copper, magnesium, and tin. Silver, gold, copper, magnesium, tin, etc. are all metals with good conductivity and ductility. By selecting the above metals, not only can the conductivity of the negative electrode material be improved, and the rate performance of the silicon-based solid-state battery be improved, but its excellent ductility can also alleviate the volume expansion problem of the silicon-based material during the charge and discharge process, thereby improving the cycle stability of the silicon-based solid-state battery. Preferably, the material of the metal nanoparticles includes at least one of silver, gold, and copper. Further preferably, the material of the metal nanoparticles is silver. Using silver as the material of the metal nanoparticles can reduce the production cost of the negative electrode material, and thus can achieve large-scale industrial promotion.
[0060] In some embodiments, the particle size of the silicon-based material is 500nm-10um. The upper limit of the particle size of the silicon-based material may be but not limited to 10um, 9um, 8um, etc., and the lower limit of the particle size of the silicon-based material may be but not limited to 500nm, 490nm, 480nm, etc.; it can be understood that the median particle size of the metal nanoparticles can also be any point value within the above range, which is not enumerated here. By limiting the particle size of the silicon-based material, it is possible to avoid the particle size of the silicon-based material being too small, resulting in a high surface energy, easy aggregation, and poor performance of the prepared negative electrode material. At the same time, it is possible to avoid the problem of low initial coulomb efficiency and poor cycle performance caused by the particle size of the silicon-based material being too small.
[0061] In some embodiments, the silicon-based material includes at least one of silicon powder, silicon carbon and silicon dioxide. Preferably, the silicon-based material is silicon powder.
[0062] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, which is applied to the negative electrode material described in the above embodiment, comprising:
[0063] S1: providing a composite of a silicon-based material and a niobium-based composite oxide;
[0064] Specifically, the silicon-based material is at least one of silicon powder, silicon carbon and silicon dioxide. Preferably, the silicon-based material is silicon powder.
[0065] Specifically, the particle size of the silicon-based material is 500nm-10um. The upper limit of the particle size of the silicon-based material can be but not limited to 10um, 9um, 8um, etc., and the lower limit of the particle size of the silicon-based material can be but not limited to 500nm, 490nm, 480nm, etc.; it can be understood that the median particle size of the metal nanoparticles can also be any point value within the above range, which is not enumerated here. By limiting the particle size of the silicon-based material, it is avoided that the particle size of the silicon-based material is too small, resulting in a high surface energy, easy aggregation, and poor performance of the prepared negative electrode material. At the same time, it is avoided that the particle size of the silicon-based material is too small, resulting in low initial coulomb efficiency and poor cycle performance.
[0066] In some embodiments, a composite of a silicon-based material and a niobium-based composite oxide is provided, comprising:
[0067] S11: providing a mixed solution including a doping material, a niobium source and a silicon-based material;
[0068] S12: Grinding the mixed solution to obtain a precursor slurry;
[0069] S13: drying the precursor slurry for a period of time to obtain a precursor material;
[0070] S14: calcining the precursor material in an oxygen-free environment to obtain a composite of the silicon-based material and the niobium-based composite oxide. In some embodiments, the doping material includes a doping element and at least one of nitrate, chloride, ethanolate, sulfate, and oxalate.
[0071] Specifically, the doping element includes at least one of transition elements, phosphorus, strontium, boron, potassium, carbon, calcium, and magnesium except niobium. Preferably, the doping element includes at least one of titanium, silver, aluminum, boron, copper, potassium, zirconium, tungsten, molybdenum, calcium, zinc, cobalt, iron, magnesium, manganese, chromium, phosphorus, bismuth, vanadium, strontium, and barium. Adding doping elements to niobium-based composite oxides can further buffer the volume change caused by the insertion and extraction of lithium ions, reduce the cracking and pulverization of the material structure, maintain the integrity of the electrode, and at the same time, the addition of doping elements can promote the transmission of lithium ions in the material, thereby improving the capacity and cycle stability of the negative electrode material. Further preferably, the doping element is zinc. Using zinc as the doping element, the stability of the prepared negative electrode material is better.
[0072] Preferably, the doping material includes nitrate and zinc element. Further preferably, the doping material is zinc nitrate. In some embodiments, the niobium source includes at least one of niobium pentoxide, niobium pentachloride, niobium ethoxide, niobium iodide, and niobium oxalate. Preferably, the niobium source includes at least one of niobium pentachloride, niobium pentoxide, and niobium ethoxide. Further preferably, the niobium source is niobium pentachloride. The use of niobium pentachloride helps to improve the overall safety of solid-state batteries. In some embodiments, in the precursor slurry, the molar ratio of the doping material to the niobium source is 1:(2-30). When the molar ratio of the doping material to the niobium source is greater than 1:30, the niobium-based composite oxide will not be able to coat the silicon-based material, thereby resulting in poor electrochemical performance of the negative electrode material, and when the molar ratio of the doping material to the niobium source is less than 1:30, the structure of the prepared negative electrode material is unstable, thereby resulting in poor electrochemical performance of the battery. Preferably, the molar ratio of the doping material to the niobium source is 1:(2-25). Further preferably, the molar ratio of the doping material to the niobium source is 1:5.
[0073] In some embodiments, in the precursor slurry, the mass ratio of the silicon-based material to the niobium source is (10-85):1. Too much silicon-based material will result in the niobium-based composite oxide being unable to coat the silicon-based material, while too little silicon-based material, although it can well coat the silicon-based material, will result in a decrease in the capacity of the prepared negative electrode material. Preferably, the mass ratio of the silicon-based material to the niobium source is (13-65):1. Further preferably, the mass ratio of the silicon-based material to the niobium source is 20:1.
[0074] In some embodiments, the grinding process includes: transferring the mixed solution to a ball mill, and wet-milling the mixed solution for a period of time to obtain a precursor slurry. Grinding the mixed solution can further reduce the particle size of the material in the mixed solution, so that the electrochemical performance of the prepared negative electrode material is better.
[0075] Specifically, the ball-to-material ratio in the grinding process is (2-30):1, the ball-milling time is 2-15h, and the ball-milling speed is 100-500r / min. By limiting the ball-to-material ratio, ball-milling time and ball-milling speed of the above-mentioned ball milling, the particle size of the material in the mixed solution is further reduced, while the production efficiency is improved and the electrochemical performance of the battery is enhanced. Preferably, the ball-to-material ratio in the grinding process is (5-15):1, the ball-milling time is 2-8h, and the ball-milling speed is 200-300r / min. Further preferably, the ball-to-material ratio in the grinding process is 10:1, the ball-milling time is 5h, and the ball-milling speed is 250r / min. In some embodiments, after step 12 and before step 13, the precursor slurry is also washed.
[0076] Specifically, the washing process includes: filtering the precursor slurry and washing it several times to obtain washed precursor slurry. In some embodiments, the drying in step S13 is performed under a vacuum environment.
[0077] In some embodiments, the drying temperature in step S13 is 50-120°C, and the drying time is 8-36h. The drying temperature and drying time in step S13 can be any point value within the above range, which is not enumerated here. By limiting the drying temperature, the effective evaporation of the solvent in the precursor slurry is avoided, and the thermal decomposition or oxidation of the precursor caused by excessive temperature is avoided. By limiting the drying time, the problem of low work efficiency caused by too long drying time is avoided. Preferably, the drying temperature in step S13 is 90-120°C, and the drying time is 10-20h. Further preferably, the drying temperature in step S13 is 100°C and the drying time is 12h.
[0078] In some embodiments, the calcination temperature in step 14 is 500-1200°C, the heating rate is 0.5-10°C / min, and the calcination time is 0.5-6h. The calcination temperature, heating rate and calcination time in step S14 can be any point value within the above range, which is not enumerated here. By limiting the range of the above calcination temperature and the heating rate, it is helpful for the grain growth, phase transformation and defect repair of the material, further improving the electrochemical performance and stability of the negative electrode material, avoiding the problem of internal stress concentration of the material caused by too fast a heating rate, and at the same time, the appropriate calcination time ensures that the crystals in the material grow fully, effectively improving the electrochemical performance of the material. Preferably, the calcination temperature is 500-800°C, the heating rate is 1-4°C / min, and the calcination time is 1-4h. Further preferably, the calcination temperature is 750°C, the heating rate is 2°C / min, and the calcination time is 3h.
[0079] In some embodiments, the oxygen-free environment in step S14 is formed by an inert atmosphere, and the inert atmosphere includes at least one of argon, a hydrogen-argon mixture, and nitrogen. Calcination in an oxygen-free environment can maintain the chemical stability of the negative electrode material. Preferably, the inert atmosphere is argon.
[0080] In some embodiments, a mixed solution containing a doping material, a niobium source and a silicon-based material is provided, including:
[0081] S110: mixing the doping material and the first solvent in a certain ratio and stirring for a period of time to obtain a first mixed solution; S111: mixing the niobium source and the second solvent in a certain ratio and stirring for a period of time to obtain a second mixed solution;
[0082] S112: The silicon-based material and the third solvent are mixed in a certain ratio and stirred for a period of time to obtain a third mixed solution; S113: The first mixed solution and the second mixed solution are added to the third mixed solution and stirred for a period of time to obtain a mixed solution containing doping material, niobium source and silicon-based material. By adopting the step-by-step mixing method, the dispersion uniformity of each material can be improved, making the precursor slurry more stable.
[0083] In some embodiments, the mass ratio of the doping material to the first solvent is 1:(2-50). Preferably, the mass ratio of the doping material to the first solvent is 1:(20-50). Further preferably, the mass ratio of the doping material to the first solvent is 1:30.
[0084] In some embodiments, the mass ratio of the niobium source to the second solvent is 1:(2-50). Preferably, the mass ratio of the niobium source to the second solvent is 1:(20-40). More preferably, the mass ratio of the niobium source to the second solvent is 1:25.
[0085] In some embodiments, the mass ratio of the silicon-based material to the third solvent is 1:(10-80). Preferably, the mass ratio of the silicon-based material to the third solvent is 1:(30-50). Further preferably, the mass ratio of the silicon-based material to the third solvent is 1:40.
[0086] By limiting the above mass ratio, the viscosity, uniformity and solid content of the subsequent precursor slurry can be improved, thereby making the structure of the negative electrode material more stable, promoting the densification and phase transition of the material, and improving the electrochemical performance and mechanical strength of the negative electrode material.
[0087] In some embodiments, the first solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, and ethyl acetate. Preferably, the first solvent is ethanol.
[0088] In some embodiments, the second solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, and ethyl acetate. Preferably, the second solvent is ethanol.
[0089] In some embodiments, the third solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, and ethyl acetate. Preferably, the third solvent is ethanol.
[0090] In some embodiments, the stirring time during the stirring process in steps S110, S111 and S112 is 2-10h, and the stirring speed is 200-600r / min. The stirring time and stirring speed during the stirring process in S110, S111 and S112 can be any point value within the above range, which is not enumerated here. By limiting the above stirring time and stirring speed, the precursor slurry prepared later is more stable. Preferably, the stirring time during the stirring process in steps S110, S111 and S112 is 2-5h, and the stirring speed is 200-400r / min. Further preferably, the stirring time during the stirring process in steps S110, S111 and S112 is 3h, and the stirring speed is 300r / min.
[0091] In some embodiments, the stirring time during the stirring process in step S113 is 3-12h, and the stirring speed is 200-600r / min. The stirring time and stirring speed during the stirring process in step S113 can be any point value within the above range, which is not enumerated here. Such arrangement can make the mixed solution stirred fully and improve work efficiency. Preferably, the stirring time during the stirring process in step S113 is 4-7h, and the stirring speed is 300-500r / min. Further preferably, the stirring time during the stirring process in step S113 is 6h, and the stirring speed is 400r / min.
[0092] S2: mixing the composite of the silicon-based material and the niobium-based composite oxide with the loaded metal source solution and stirring for a period of time to obtain a composite intermediate solution;
[0093] Specifically, a composite of a silicon-based material and a niobium-based composite oxide is mixed with a loaded metal source solution and stirred for a period of time to obtain a composite intermediate solution, including: mixing a loaded metal source with a fourth solvent to obtain a loaded metal source solution, adding a composite of a silicon-based material and a niobium-based composite oxide to the loaded metal source solution, mixing and stirring for a period of time to obtain a composite intermediate solution.
[0094] Specifically, the stirring time in the preparation of the composite intermediate solution is 2 h, and the stirring rate is 400 r / min.
[0095] In some embodiments, before adding the composite of the silicon-based material and the niobium-based composite oxide to the loaded metal source solution and mixing and stirring for a period of time, the composite of the silicon-based material and the niobium-based composite oxide needs to be ground. This arrangement enables the composite to fully react with the loaded metal source solution, further improving the conductivity of the negative electrode material.
[0096] In some embodiments, the stirring time during the stirring process in step S2 is 1-5h, and the stirring speed is 200-600r / min. The stirring time and stirring speed during the stirring process in step S2 can be any point value within the above range, which is not enumerated here. Under this stirring time and stirring speed, the loaded metal source solution can be fully infiltrated into the composite, so that in the subsequent reduction process, there are more loaded nanoparticles on the composite, further improving the conductivity of the negative electrode material. Preferably, the stirring time during the stirring process in step S2 is 1-3h, and the stirring speed is 300-500r / min. Further preferably, the stirring time during the stirring process in step S2 is 2h, and the stirring speed is 400r / min.
[0097] In some embodiments, the mass ratio of the composite of the loaded metal source and the silicon-based material and the niobium-based composite oxide is 1:(45-90). By limiting the above mass ratio, the problem of excessive amount of the loaded metal source causing a decrease in the capacity and energy density of the battery is avoided, while the problem of poor conductivity of the prepared negative electrode material caused by too little amount of the loaded metal source is avoided. Preferably, the mass ratio of the composite of the loaded metal source and the silicon-based material and the niobium-based composite oxide is 1:(50-90). Further preferably, the mass ratio of the composite of the loaded metal source and the silicon-based material and the niobium-based composite oxide is 1:60.
[0098] In some embodiments, the loaded metal source includes at least one of a silver source, a gold source, a copper source, a magnesium source, and a tin source. Silver, gold, copper, magnesium, tin, etc. are metals with good conductivity and ductility. By selecting the above metals, not only can the conductivity of the negative electrode material be improved, but also the rate performance of the silicon-based solid-state battery can be improved. Its excellent ductility can alleviate the volume expansion problem of the silicon-based material during the charge and discharge process, thereby improving the cycle stability of the silicon-based solid-state battery. Preferably, the loaded metal source includes at least one of a silver source, a gold source, and a copper source. Further preferably, the loaded metal source is a silver source. Using a silver source as a loaded metal source can reduce the production cost of the negative electrode material, thereby enabling large-scale industrial promotion.
[0099] Specifically, the silver source includes at least one of silver ammonia, silver nitrate, silver periodate, silver fluoride, silver perchlorate, silver carbonate, and silver acetate. Preferably, the silver source is silver nitrate.
[0100] In some embodiments, the fourth solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, and ethyl acetate. Preferably, the fourth solvent is deionized water.
[0101] S3: performing reduction treatment on the composite intermediate solution to obtain a silicon-based composite negative electrode material.
[0102] In some embodiments, the composite intermediate solution is subjected to reduction treatment to obtain a silicon-based composite negative electrode material, including: mixing the composite intermediate solution with a reducing agent and stirring for a period of time to obtain a reduced composite intermediate solution, filtering, washing and drying the reduced composite intermediate solution to obtain a silicon-based composite negative electrode material.
[0103] In some embodiments, the reducing agent includes at least one of dimethyl sulfoxide, ethylene glycol, glucose, sodium bisulfite, hydrazine hydrate, sodium borohydride, hydrogen peroxide, ascorbic acid, lithium aluminum hydride, and sodium hypophosphite. Preferably, the reducing agent is ethylene glycol.
[0104] In some embodiments, the stirring time during the stirring process in step S3 is 1-5h, and the stirring speed is 200-600r / min. The stirring time and stirring speed during the stirring process in step S3 can be any point value within the above range, which is not enumerated here. Such an arrangement can make the composite intermediate solution and the reducing agent fully mixed, and can make the metal nanoparticles on the niobium-based composite oxide more fully reduced, further improving the electrochemical performance of the negative electrode material. Preferably, the stirring time during the stirring process in step S3 is 2-4h, and the stirring speed is 400-600r / min. Further preferably, the stirring time during the stirring process in step S3 is 3h, and the stirring speed is 500r / min.
[0105] In some embodiments, the drying temperature in the drying process in step S3 is 50-120°C, and the drying time is 12-36h. The drying temperature and drying time in the drying process in step S3 can be any point value within the above range, which are not enumerated here. Preferably, the drying temperature in the drying process in step S3 is 80-120°C, and the drying time is 12-24h. Further preferably, the drying temperature in the drying process in step S3 is 100°C, and the drying time is 12h.
[0106] This embodiment also provides a method for preparing a solid-state battery using the above-mentioned negative electrode material, comprising:
[0107] S4: mixing the binder and the fifth solvent and dispersing them for a period of time to obtain a glue solution;
[0108] In some embodiments, the binder includes at least one of polyurethane, polyvinylidene fluoride, polyvinylidene chloride, polytetrafluoroethylene, polyacrylic acid, polyethylene oxide, polypropylene oxide, polyoxyethylene, polyimide, polymethyl methacrylate, polycarbonate, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylonitrile or sodium carboxymethyl cellulose. Preferably, the binder is polyvinylidene fluoride.
[0109] In some embodiments, the fifth solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, ethyl acetate, and N-methylphthalimide. Preferably, the fifth solvent is N-methylphthalimide.
[0110] In some embodiments, the dispersion time in step S4 is 6-12 hours, and the solid content of the glue is 0.3-7%. Preferably, the dispersion time in step S4 is 8-12 hours, and the solid content of the glue is 0.5-2.5%. Further preferably, the dispersion time in step S4 is 10 hours, and the solid content of the glue is 1%.
[0111] S5: mixing the glue solution, the silicon-based composite negative electrode material and the sixth solvent in a certain ratio and dispersing them for a period of time to obtain a slurry;
[0112] In some embodiments, the sixth solvent includes at least one of deionized water, acetonitrile, ethanol, n-hexane, n-heptane, tetrahydrofuran, 2-methyltetrahydrofuran, anisole, dimethyl ether, dimethyl sulfone, toluene, xylene, trimethylbenzene, glycol ether, dichloroethane, N,N-dimethylformamide, benzene, chlorobenzene, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate, and ethyl acetate. Preferably, the sixth solvent is N-methylphthalimide.
[0113] In some embodiments, in the slurry, the mass ratio of the silicon-based composite negative electrode material to the binder is (95-100): (0-5). Preferably, in the slurry, the mass ratio of the silicon-based composite negative electrode material to the binder is 98:2. In some embodiments, the dispersion time in step S5 is 4-12 hours, and the solid content of the slurry is 15-65%. Preferably, the dispersion time in step S5 is 5 hours, and the solid content of the slurry is 45%.
[0114] S6: coating the slurry on a copper foil to obtain a prefabricated negative electrode sheet, and drying the prefabricated negative electrode sheet to obtain a negative electrode sheet.
[0115] Specifically, the coating method is extrusion spraying.
[0116] Specifically, the drying process includes: drying the prefabricated negative electrode sheet at a first temperature, and then placing it in a vacuum oven and drying it at a second temperature for a period of time to obtain the negative electrode sheet.
[0117] In some embodiments, the first temperature is 50-150° C. The first temperature can be any point value within the above range, which is not enumerated here. Preferably, the first temperature is 100° C.
[0118] In some embodiments, the second temperature is 80-180°C, and the drying time is 12-36 hours. The second temperature and time can be any point value within the above range, which is not enumerated here. Preferably, the second temperature is 120°C, and the drying time at the second temperature is 24 hours.
[0119] In some embodiments, after the prefabricated negative electrode sheet is dried, a hot rolling process is further performed.
[0120] Specifically, the temperature during the hot roller pressing process is 40-80° C. Preferably, the temperature during the hot roller pressing process is 50° C.
[0121] S7: Assemble the negative electrode plate and the lithium metal plate into a principle battery, and use a solid electrolyte as the middle layer to obtain a solid-state battery.
[0122] In some embodiments, the solid electrolyte includes at least one of LGPS, LPS, LPSC, LPSBr, LPSI, LSiPS, LGSiPS, LIC, LYC, LYB, LAC, and LZC. Preferably, the solid electrolyte is LPSC.
[0123] The following is an introduction to the specific embodiments of the present application in conjunction with the above-mentioned positive electrode material for sodium ion batteries, its preparation method and sodium ion battery. The following examples describe the technical solution of the present application in more detail, and these examples are only for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the examples can be obtained commercially or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the examples can be commercially available.
[0124] Example 1
[0125] This embodiment provides a method for preparing a silicon-based composite negative electrode material, which specifically includes the following steps:
[0126] S1: 50 g of silicon powder was dissolved in anhydrous ethanol, and stirred on a magnetic stirrer at 300 r / min for 3 h to obtain a first mixed solution, 0.35 g of zinc nitrate was dissolved in anhydrous ethanol, and stirred on a magnetic stirrer at 300 r / min for 3 h to obtain a second mixed solution, 2.5 g of niobium pentachloride was dissolved in anhydrous ethanol, and stirred on a magnetic stirrer at 300 r / min for 3 h to obtain a third mixed solution, wherein the median particle size of the silicon powder was 500 nm-10 um, the mass ratio of zinc nitrate to anhydrous ethanol in the first mixed solution was 1:30, the mass ratio of niobium pentachloride to anhydrous ethanol in the second mixed solution was 1:25, and the mass ratio of silicon powder to anhydrous ethanol in the third mixed solution was 1:40.
[0127] S2: The second mixed solution and the first mixed solution were added to the third mixed solution in sequence, and stirred for 6 hours at a stirring speed of 400 r / min to obtain a mixed solution containing zinc nitrate, silicon powder and niobium pentachloride. The mixed solution was transferred to a ball mill, and a ball with a diameter of The precursor slurry is ground with zirconium oxide balls to obtain a precursor slurry, wherein the ball-to-material ratio during the grinding process is 10:1, the ball milling time is 5 hours, the ball milling speed is 250r / min, the precursor slurry is filtered and washed several times, and then placed in a vacuum oven and dried at 80°C for 24 hours to obtain a precursor material, wherein the molar ratio of zinc nitrate to niobium pentachloride is 1:5, and the mass ratio of silicon powder to niobium pentachloride is 20:1;
[0128] S3: placing the precursor material in an argon atmosphere protection furnace, calcining at 750°C for 3 hours at a heating rate of 2°C / min, and obtaining a composite of silicon-based material and niobium-based composite oxide after cooling in the furnace;
[0129] S4: Dissolve 0.67g of silver nitrate in deionized water to obtain a loaded metal source solution, mix the loaded metal source solution and 40g of a composite of a silicon-based material and a niobium-based composite oxide, stir for 2h at a stirring speed of 400r / min to obtain a composite intermediate solution, add 2g of ethylene glycol to the composite intermediate solution, stir for 3h at a stirring speed of 500r / min to obtain a reduced composite intermediate solution, filter and wash the reduced composite intermediate solution, and dry it in a vacuum oven at a temperature of 100°C for 12h to obtain a silicon-based composite negative electrode material, wherein the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:60.
[0130] The solid-state battery is prepared by using the above silicon-based composite negative electrode material, and the preparation method is as follows:
[0131] Polyvinylidene fluoride and N-methylphthalimide were mixed by a double planetary mixer and dispersed for 10 hours to obtain a glue with a solid content of 1%, and then the glue and silicon-based composite negative electrode material were mixed by a double planetary mixer and dispersed for 5 hours to obtain a slurry with a solid content of 45%. In the slurry, the mass ratio of the silicon-based composite negative electrode material to polyvinylidene fluoride was 98:2. The prepared slurry was applied to a copper foil by extrusion spraying on a coating machine to obtain a prefabricated negative electrode sheet. The prefabricated negative electrode sheet was dried at 100°C and then transferred to a vacuum oven at 120°C for drying for 24 hours, and then hot rolled at 50°C to obtain a negative electrode sheet. The negative electrode sheet was cut into 1 cm 2 The disc is assembled with a lithium metal sheet into a principle battery. The middle layer uses 90mg of sulfide solid electrolyte LPSC to obtain a fully solid-state battery, and a pressure of 10MPa is applied to the stack. The electrochemical performance test is carried out using a Xinwei battery tester, with a charge and discharge range of 0.01-2.5V and a charge and discharge rate of 0.1-5C.
[0132] Example 2
[0133] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the molar ratio of zinc nitrate to niobium pentachloride is 1:2.
[0134] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0135] Example 3
[0136] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the molar ratio of zinc nitrate to niobium pentachloride is 1:25.
[0137] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0138] Example 4
[0139] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of silicon powder to niobium pentachloride is 13:1.
[0140] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0141] Example 5
[0142] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of silicon powder to niobium pentachloride is 65:1.
[0143] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0144] Example 6
[0145] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of silicon powder to niobium pentachloride is 40:1.
[0146] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0147] Example 7
[0148] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:80.
[0149] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0150] Example 8
[0151] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:50.
[0152] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0153] Example 9
[0154] This embodiment provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:90.
[0155] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0156] Comparative Example 1
[0157] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that zinc nitrate is not added.
[0158] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0159] Comparative Example 2
[0160] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that zinc nitrate and niobium pentachloride are not added.
[0161] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0162] Comparative Example 3
[0163] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that no silver nitrate is added.
[0164] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0165] Comparative Example 4
[0166] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that zinc nitrate, niobium pentachloride and silver nitrate are not added.
[0167] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0168] Comparative Example 5
[0169] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that the molar ratio of zinc nitrate to niobium pentachloride is 1:0.5.
[0170] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0171] Comparative Example 6
[0172] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that the molar ratio of zinc nitrate to niobium pentachloride is 1:50.
[0173] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0174] Comparative Example 7
[0175] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that the mass ratio of silicon powder to niobium pentachloride is 7:1.
[0176] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0177] Comparative Example 8
[0178] This comparative example provides a method for preparing a silicon-based composite negative electrode material, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of silicon powder to niobium pentachloride is 110:1.
[0179] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0180] Comparative Example 9
[0181] This comparative example provides a method for preparing a silicon-based composite negative electrode material. The same points as those in Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:20.
[0182] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0183] Comparative Example 10
[0184] This comparative example provides a method for preparing a silicon-based composite negative electrode material. The similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of the composite of silver nitrate to the silicon-based material and the niobium-based composite oxide is 1:120.
[0185] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0186] Comparative Example 11
[0187] This comparative example provides a method for preparing a silicon-based composite negative electrode material. The similarities with Example 1 are not repeated here. The difference between this method and Example 1 is that the loaded metal source silver nitrate is replaced by bismuth nitrate.
[0188] Furthermore, the anode material obtained as described above is used to prepare a solid-state battery, and the specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and will not be described in detail.
[0189] The above examples and comparative examples adopt the following test methods: 1: The thickness of the niobium-based composite oxide coated on the surface of the silicon-based material and the thickness of the metal nanoparticles loaded on the composite in the silicon-based composite materials obtained in the examples and comparative examples are tested by using a transmission electron microscope (model JSM-2100F) for measurement and observation, and the test results are shown in Table 1. 2. The batteries prepared in the examples and comparative examples are subjected to charge and discharge tests using a Xinwei battery test system, with the charge and discharge range set to 0.01-2.5V and the charge and discharge rate set to 0.1-5C, and the prepared solid-state batteries are subjected to constant current charge and discharge cycle tests, and the test results are shown in Table 2.
[0190] The following table 1 statistically records the test data in the embodiments and comparative examples:
[0191] Table 1
[0192]
[0193]
[0194] Table 2
[0195]
[0196]
[0197] With reference to Table 1, Table 2 and the accompanying drawings, in combination with Examples 1, 2 and 3, it can be seen that, with other conditions remaining unchanged, a larger or smaller molar ratio of zinc nitrate to niobium pentachloride will result in slightly different electrochemical properties of the prepared battery.
[0198] In combination with Examples 1, 4, 5, and 6, it can be seen that the content ratio of niobium pentachloride to silicon powder has an important influence on the electrochemical properties of the negative electrode material. When the amount of silicon powder is too much, the niobium-based composite oxide will not be able to coat the silicon powder, thereby affecting the cycle capacity retention rate of the prepared battery. Although a small amount of silicon powder can better coat the silicon-based material, it will cause a significant decrease in the charging capacity of the prepared battery.
[0199] In combination with Examples 1, 7, 8, and 9, it can be seen that the content of the composite of silver and niobium-based composite oxides also has an important influence on the electrochemical properties of the negative electrode material. When the silver content is too much, the capacity and energy density of the battery are significantly reduced. When the silver content is too little, the conductivity of the prepared electrode material is poor, which leads to a decrease in the electrochemical performance of the battery.
[0200] Combining Examples 1-3 and Comparative Examples 1, 5, and 6, it can be seen that the content of zinc and niobium in the niobium-based composite oxide has an important influence on the electrochemical performance of the negative electrode material. When other conditions remain unchanged and zinc nitrate is not added, the niobium-based composite oxide coated on the silicon-based material becomes a niobium-based oxide. Compared with the niobium-based oxide, the niobium-based composite oxide can provide more redox electron pairs, so that the negative electrode material has a higher capacity and energy density. Secondly, the niobium-based composite oxide has higher electrical conductivity and structural stability, and its multi-metal interaction can form a fast lithium insertion and extraction channel, which can improve the rate performance and cycle performance of the negative electrode material.
[0201] In combination with Example 1, Examples 4-6 and Comparative Examples 2, 7, and 8, it can be seen that, when other conditions remain unchanged, the lack of a coating layer of a niobium-based composite oxide in the negative electrode material greatly reduces the structural stability of the silicon-based material, increases side reactions, and greatly reduces the capacity and cycle performance of the negative electrode material. If the niobium-based composite oxide layer is too thick, not only will the proportion of the active material silicon-based material be greatly reduced, thereby reducing the energy density of the battery, but it will also hinder the diffusion of lithium ions and increase the interface impedance, thereby reducing the rate performance and cycle life of the negative electrode material.
[0202] In combination with Example 1, Examples 7-9 and Comparative Examples 3, 9, and 10, it can be seen that, when other conditions remain unchanged, the negative electrode material does not include or contains less nanosilver, which reduces the conductivity of the negative electrode material. In addition, the first coulombic efficiency and rate performance of the negative electrode material are significantly reduced. This is mainly because the presence of the nanosilver layer can optimize the interface contact between the negative electrode and the solid electrolyte, forming a three-dimensional cross-linked conductive network, thereby improving the first coulombic efficiency and rate performance of the negative electrode material. Excessive nanosilver content will reduce the reversible capacity and first coulombic efficiency of the negative electrode material, thereby reducing the energy density of the battery.
[0203] Combining Example 1 and Comparative Example 4, it can be seen that other conditions remain unchanged, and the negative electrode material in Comparative Example 4 only includes silicon-based materials, which significantly reduces the capacity and first coulomb efficiency of the battery. This is mainly due to the lack of niobium-based composite oxides in the composite material structure in the silicon-based solid-state battery system. At low potentials, the silicon-based material and the solid electrolyte will have side reactions, and the silicon-based material lacks a coating layer that can buffer volume changes, and the cycle life is further reduced. The niobium-based composite oxide coating layer of suitable thickness has almost no volume change during the charge and discharge process, which can maintain the stability of the electrode structure, reduce the pulverization and failure of the silicon material, and help improve the first coulomb efficiency and cycle performance of the material. On the other hand, the nanosilver coating layer of suitable thickness in the negative electrode material can greatly improve the conductivity of the silicon-based negative electrode and the niobium-based composite oxide, improve the electron conduction rate, reduce the overpotential of the silicon-based negative electrode in the solid-state system, and alleviate the volume expansion of the silicon-based material, enhancing the rate performance and charge and discharge stability of the negative electrode material of the solid-state battery.
[0204] Combining Example 1 and Comparative Example 11, it can be seen that when other conditions remain unchanged, nanosilver in the negative electrode material is replaced with nanobismuth. Since bismuth has poor electrical conductivity relative to silver, the rate performance of the negative electrode material is seriously affected. Secondly, the interface stability between bismuth and the solid electrolyte is poor, and the alloying of bismuth and lithium during the charge and discharge process is accompanied by a large volume expansion, which will lead to particle pulverization and thus reduce the cycle life of the battery.
[0205] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.
Claims
1. A silicon-based composite negative electrode material, characterized in that: The negative electrode material comprises a composite of a silicon-based material and a niobium-based composite oxide, and metal nanoparticles supported on the composite, and at least a portion of the niobium-based composite oxide is coated on the surface of the silicon-based material.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following characteristics: The thickness of the niobium-based composite oxide coated on the surface of the silicon-based material is 200nm-2um; The loading thickness of the metal nanoparticles on the composite is 30nm-500nm.
3. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following characteristics: The median particle size of the metal nanoparticles is 10nm-150nm; The particle size of the silicon-based material is 500nm-10um.
4. The negative electrode material according to any one of claims 1 to 3, characterized in that The material of the metal nanoparticles includes at least one of silver, gold, copper, magnesium and tin.
5. The negative electrode material according to any one of claims 1 to 3, characterized in that: The niobium-based composite oxide includes niobium and doping elements, and the doping element includes at least one of transition elements other than niobium, phosphorus, strontium, boron, potassium, carbon, calcium, and magnesium.
6. A method for preparing a silicon-based composite negative electrode material, applied to the negative electrode material according to any one of claims 1 to 5, characterized in that: include: S1: providing a composite of a silicon-based material and a niobium-based composite oxide; S2: mixing the composite of the silicon-based material and the niobium-based composite oxide with a loaded metal source solution and stirring for a period of time to obtain a composite intermediate solution; S3: performing reduction treatment on the composite intermediate solution to obtain a silicon-based composite negative electrode material.
7. The preparation method according to claim 6, characterized in that: The reduction treatment of the composite intermediate solution to obtain the silicon-based composite negative electrode material includes: mixing the composite intermediate solution with a reducing agent and stirring for a period of time to obtain a reduced composite intermediate solution; and drying the reduced composite intermediate solution to obtain the silicon-based composite negative electrode material.
8. The preparation method according to claim 7, characterized in that: The preparation method meets at least one of the following characteristics: The stirring time in the stirring process in step S2 is 1-5h, and the stirring speed is 200-600r / min; The stirring time in the stirring process in step S3 is 1-5h, and the stirring speed is 200-600r / min; The drying temperature in the drying process in step S3 is 50-120° C., and the drying time is 12-36 hours.
9. The preparation method according to claim 6, characterized in that: A composite of the silicon-based material and niobium-based composite oxide is provided, comprising: S11: providing a mixed solution including a doping material, a niobium source and a silicon-based material; S12: Grinding the mixed solution to obtain a precursor slurry; S13: drying the precursor slurry for a period of time to obtain a precursor material; S14: calcining the precursor material in an oxygen-free environment to obtain a composite of the silicon-based material and the niobium-based composite oxide.
10. The preparation method according to claim 9, characterized in that: The preparation method meets at least one of the following characteristics: In the precursor slurry, the molar ratio of the doping material to the niobium source is 1:(2-30); In the precursor slurry, the mass ratio of the silicon-based material to the niobium source is (10-85):
1. In the composite intermediate solution, the mass ratio of the supported metal source to the composite of the silicon-based material and the niobium-based composite oxide is 1:(45-90).
11. The preparation method according to claim 9, characterized in that: The method of providing a mixed solution containing a doping material, a niobium source and a silicon-based material comprises: S110: mixing the doping material and the first solvent in a certain ratio and stirring for a period of time to obtain a first mixed solution; S111: mixing the niobium source and the second solvent in a certain ratio and stirring for a period of time to obtain a second mixed solution; S112: mixing the silicon-based material and the third solvent in a certain ratio and stirring for a period of time to obtain a third mixed liquid; S113: adding the first mixed solution and the second mixed solution to the third mixed solution, mixing and stirring for a period of time to obtain the mixed solution containing the doping material, the niobium source and the silicon-based material.
12. The preparation method according to any one of claims 9 to 11, characterized in that: The preparation method meets at least one of the following characteristics: The stirring time in the stirring process in steps S110, S111 and S112 is 2-10 hours, and the stirring speed is 200-600 r / min; The stirring time in the stirring process in step S113 is 3-12 hours, and the stirring speed is 200-600 r / min; The ball-to-material ratio in the grinding process in step S12 is (2-30):1, the ball milling time is 2-15h, and the ball milling speed is 100-500r / min; The drying temperature in step S13 is 50-120°C and the drying time is 8-36h; The calcination temperature in step S14 is 500-1200°C, the heating rate is 0.5-10°C / min, and the calcination time is 0.5-6h; The oxygen-free environment in step S14 is formed by an inert atmosphere, and the inert atmosphere includes at least one of argon, hydrogen-argon mixed gas and nitrogen.
Citation Information
Cited By
Niobium-based compound / silicon carbon composite material and preparation method and application thereof
CN121641926A
A niobium-based compound / silicon-carbon composite material, a preparation method and application thereof
CN121641926B